TRANSPARASI DAN AKUNTABILITAS DALAM PENCEGAHAN FRAUD DIINSTANSI PEMERINTAH (STUDI KASUS KANTOR KEC. CIWIDEY) - Idah Rosidah; Gunardi; Priatna Kesumah; Royke Bahagia Rizka (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
This research analyzes the level of transparency, accountability practices, and effectiveness of the fraud prevention system at the Ciwidey District Office with the aim of evaluating administrative integrity and government efforts to provide quality public services. The method used is a qualitative approach through case studies with in-depth interviews with staff and office officials. The research results highlight a lack of transparency in information related to policy and finance, accompanied by a decision-making process that is not always clear. The accountability system is also not optimal in ensuring accountability for actions taken. Documentation analysis shows that the internal control system is not fully effective in preventing cases of fraud. From the results of this research, it was concluded that urgent improvements are needed in increasing information transparency, strengthening accountability practices, and optimizing fraud prevention systems. Recommendations include increasing the availability of open information, increasing awareness of responsible actions, and implementing concrete steps to strengthen internal control. Implementation of these recommendations is expected to improve the quality of public services, improve the image of government institutions, and provide a stronger foundation for the Ciwidey District Office and other government institutions in maintaining the integrity and trust of the public.